Greenhouse Potential based on Ecotourism and Education for Sustainable Village Economic Resilience - Lilik Nurindah Sari; Tutik Nurhidayati; Maya Shovitri; Enny Zulaika; Nengah Dwianita Kuswytasari; Arif Luqman; Nur Hidayatul Alami; Kristanti Indah Purwani; Nurul Jadid; Dini Ermavitalini; Imam Wahyudi Farid; Ciptian Weried Priananda (IPTEK Journal of Proceedings Series, 2023)
Indonesia has many rural areas with diversity and uniqueness in each region that have developed into eco-tourism. The village that is being developed as an eco-tourism destination is expected to improve the welfare of the surrounding community. Developed eco-tourism can provide jobs for residents in the village. Eco-tourism is also one of the developments to preserve ecosystems in rural areas. This eco- tourism sector can support community welfare and sustainable rural development. One approach to the development of rural areas is through village ecotourism. Village Ecotourism is a rural area with several special characteristics that can be used as a tourist destination. One way to improve the development of village ecotourism is by adding new facilities that lead to educational tourism, i.e., greenhouse facilities. The existence of this greenhouse can be used as a means of science education about a more advanced agricultural system with a controlled environmental system. Greenhouse technology can improve the quality and quantity of plant productivity, thereby increasing people's income, and producing healthier organic plant products. Greenhouses can also be used as educational tourism facilities for various science education activities and simple agricultural training. Training for residents can also be carried out, for community empowerment, such as training in planting, fertilizing, nurseries, processing plant products, and the process of packaging plant products. This review summarizes the various potentials of Greenhouse development for the development of education-based village ecotourism and provides references for further research that focuses on community service, which is increasing sustainable village economic resilience.